Becoming agile - Worley, Christopher G. (Jossey-Bass, a Wiley Brand, 2015)
Becoming Agile: How the SEAM Approach to Management Builds Adaptability illustrates the process of becoming an agile organization. Reflecting the principles presented in The Agility Factor, readers are taken on a real-world journey of transformation and change. This short-format case study of the French company Brioche Pasquier highlights how one organization successfully implemented the principles of agility using the socio-economic approach to management, detailing each step of the process and describing how every decision brought the goal closer within reach. Readers get inside the heads of decision makers to gain insight into how tough decisions were made, how new, important, and flexible management tools were implemented, and how the necessary changes ultimately benefitted both the organization and the people who made it work